Compounding care burdens: women's everyday experiences of climate preparedness and adaptation in Banaskantha, India - Bachina, Vinitha; Sheth, Megha; Srivastava, Shilpi (Gender and development, 2025)
As rapid climate change is increasing the occurrence of extreme weather events, there is a noticeable increase in co-located hazards which refer to climate events that overlap or occur concurrently (e.g. droughts followed by floods or overlapping with heatwaves). Regions that are historically unaccustomed to these patterns of high variability are now struggling to adapt to these unpredictable variations. Drawing on evidence from the ANTICIPATE project, we argue that such co-located hazards not only compound or intensify impacts due to the intersection of these extremes but also add an additional dimension of gendered vulnerability. Using the lens of intersectionality and care, we show how women are at the frontline of preparedness, for such extremes, despite absorbing a disproportionate amount of the impacts of these shocks and slow-onset hazards. However, owing to gendered vulnerability, their work remains unrecognised and hidden, thus leaving them out of decision-making spaces. In this paper, we demonstrate how women's contributions towards building preparedness at an everyday level are crucial to household adaptation in the face of increasing climatic uncertainties.